To Create or to Redistribute? That is the Question - Koursaros, Demetris; Savva, Christos S.; Michail, Nektarios A.; Papadopoulou, Niki (My University, 2024)
This study delves into the persistent low GDP growth observed in the post-crisis period, despite aggressive financial easing measures. It explores how economic agents allocate available funds, either through investments in new capital creation or the acquisition of existing assets for capital gains (asset redistribution). The former approach bolsters total income and employment, while the latter reshapes wealth distribution among agents. Through a combination of theoretical insights and empirical evidence, we argue that during economic downturns, investors often find it more lucrative, and lenders consider it safer, to finance the repurchasing of existing assets rather than investing in new ones. This trend not only worsens recessions but also hampers the recovery process by limiting entrepreneurs’ access to funding and altering the economy’s capital structure. Moreover, given that asset redistribution tends to benefit the wealthy, a surge in inequality fosters a cycle of income redistribution, further exacerbating economic downturns.
Keywords: inequality; capital misallocation; investment; business cycles; asset redistribution